Devising a method for assessing the efficiency in managing logistics operations of motor transport enterprises - Vorkut, Tatiana; Volynets, Lyudmila (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the logistics operations of a motor transport company. The task addressed is to improve the effectiveness of assessing the state of efficiency in managing logistics activities of motor vehicle enterprises, regardless of the level of hierarchy of the motor vehicle enterprise. Underlying the research is the game chaos algorithm (GCA) applied for assessing the state of efficiency in managing the logistics operations of motor transport enterprises. Evolving artificial neural networks are used to train GCA. A comprehensive model for assessing the effectiveness of the operation of logistics activities of motor transport enterprises was built. The model is proposed to be used in the operational management of logistics activities of motor transport enterprises. In addition, the model built allows for the following: − assessing possible risks of disrupting the task of providing goods and services in organizations and organizational networks; − determining the influence of performance evaluation indicators of the logistic support system in organizations and organizational networks on each other; – establishing the influence of a group of indicators for evaluating the effectiveness of logistics support in organizations and organizational networks on a separate indicator. The study also proposes a method for evaluating the effectiveness of managing logistics activities of motor transport enterprises. The originality of the method is that it makes it possible to avoid hitting the global and local optimum due to additional improved procedures based on the use of game chaos theory. The simulation results showed an increase in the effectiveness of assessing the operational efficiency of the management of logistics activities of motor transport enterprises at the level of 14–16 % due to the use of additional improved procedures